Neutrophil Gelatinase Associated Lipocalin Levels in Normal Pregnancy and Preeclampsia Subtypes - Ridho Berkah Pramuditha; Vaulinne Basyir; Firdawati Firdawati; Mondale Saputra; Roza Sri Yanti; Hudila Rifa Karmia (Andalas Obstetrics And Gynecology Journal, 2026)
Background: Preeclampsia is still a major cause of morbidity and mortality in pregnant women. Neutrophil gelatinase–associated lipocalin (NGAL) is a better biomarker than creatinine as a biomarker of kidney disorders and is considered as an accurate early predictor of preeclampsia. However, the results of studies related to this still vary Objective: To determine the differences in neutrophil gelatinase associated lipocalin (NGAL) expression in normal pregnancy, early-onset preeclampsia (EOP) and late-onset preeclampsia (LOP). Methods: This is a cross-sectional study conducted from April 2024 to June 2025. The samples were all pregnant women aged ≥20 weeks who came to the Obstetrics Department at Dr. M. Djamil General Hospital, Andalas University Hospital and dr. Reksodiwiryo Hospital in Padang City who met the inclusion and exclusion criteria. Patients with a history of malignancy, infection, premature rupture of membranes, or having comorbidities were excluded from the study. Patients were divided into normal pregnancy, EOP and LOP. Examination of NGAL levels from venous blood samples was carried out using the ELISA. Results: In this study, there were 12 normal pregnancies, 13 EOP pregnancies and 11 LOP pregnancies. Each group of pregnant women had almost similar characteristics with an average age of 31 years and the majority of patients being multiparous, obese, having a high school education and being housewives. In this study, NGAL levels were 2.45 ± 0.73 ng/ml; 3.61 ± 1.12 ng/ml; and 3.63 ± 1.12 in normal pregnancies, EOP, and LOP, respectively. The ANOVA test obtained p value of 0.01, which means that there is a significant difference in NGAL expression between normal pregnancies, EOP and LOP. The post hoc test obtained significant differences between NGAL level of normal pregnancy with EOP (p = 0.021) and normal pregnancy with LOP (p = 0.027), but not in NGAL expression between EOP with LOP (p = 1,000). Conclusion: Differences in NGAL expression were found to be significant between normal pregnancy and EOP and LOP. Meanwhile, there was no difference in NGAL expression between EOP and LOP.